Parental magma, magmatic stratigraphy, and reef-type PGE enrichment of the 2.44-Ga mafic-ultramafic Näränkävaara layered intrusion, Northern Finland - Järvinen, Ville; Halkoaho, Tapio; Konnunaho, Jukka; Heinonen, Jussi S.; Rämö, O. Tapani (Mineralium Deposita, 2021)
About 20 mafic-ultramafic layered intrusions in the northern Fennoscandian shield were emplaced during a widespread magmatic event at 2.5-2.4 Ga. The intrusions host orthomagmatic Ni-Cu-PGE and Cr-V-Ti-Fe deposits. We update the magmatic stratigraphy of the 2.44-Ga Näränkävaara mafic-ultramafic body, northeastern Finland, on the basis of new drill core and outcrop observations. The Näränkävaara body consists of an extensive basal dunite (1700 m thick), and a layered series comprising a peridotitic-pyroxenitic ultramafic zone (600 m thick) and a gabbronoritic-dioritic mafic zone (700 m thick). Two reversals are found in the layered series. The composition of the layered series parental magma was approximated using a previously unidentified marginal series gabbronorite. The parental magma was siliceous high-Mg basalt with high MgO, Ni, and Cr, but also high SiO2 and Zr, which suggests primary magma contamination by felsic crust. Cu/Pd ratio below that of primitive mantle implies PGE-fertility. The structural position of the marginal series indicates that the thick basal dunite represents an older wallrock for the layered intrusion. A subeconomic reef-type PGE-enriched zone is found in the border zone between the ultramafic and mafic zones and has an average thickness of 25 m with 150-250 ppb of Pt + Pd + Au. Offset-type metal distribution and high sulfide tenor (50-300 ppm Pd) and R-factor (105) suggest reef formation by sulfide saturation induced by fractional crystallization. The reef-forming process was probably interrupted by influx of magma related to the first reversal. Metal ratios suggest that this replenishing magma was PGE-depleted before emplacement. Peer reviewed